Characterisation of curli production, cell surface hydrophobicity, autoaggregation and attachment behaviour of escherichia coli O157 - Goulter, R.; Gentle, I.; Dykes, Gary (2010)
Escherichia coli O157 are an important group of foodborne pathogens with the ability to attach to materials commonly used in food processing environments such as slightly hydrophilic stainless steel. The aim of this study was to characterise six E. coli isolates, including five E. coli O157, for curli production, autoaggregation, hydrophobicity and attachment to highly hydrophilic glass and hydrophobic Teflon®. Curli production and autoaggregation were determined using absorbance assays; hydrophobicity by bacterial adherence to hydrocarbons, hydrophobic interaction chromatography and contact angle measurements; and attachment using epifluorescence microscopy. Curli production varied between strains and for some strains correlated with autoaggregation. Curli production correlated with decreased hydrophobicity for two strains. Four of the six isolates increased attachment to glass, but decreased attachment to Teflon® with increased curli production. In contrast, one of the six isolates decreased attachment to glass, but increased attachment to Teflon® with increasing curli production. Curli production by the remaining isolate did not correlate with hydrophobicity or attachment. Attachment of some E. coli, including E. coli O157, to abiotic surfaces may be influenced by curli production, autoaggregation and hydrophobicity. However, for other strains, a variety of factors may be of greater influence on these properties and ability to attach to abiotic surfaces. This study highlights the complexity of bacterial surface properties and their relationship with bacterial attachment. © 2010 Springer Science+Business Media, LLC.